1996
DOI: 10.1063/1.360821
|View full text |Cite
|
Sign up to set email alerts
|

Sequential phase formation by ion-induced epitaxy in Fe-implanted Si(001). Study of their properties and thermal behavior

Abstract: The epitaxial growth of FeSi2 silicides was studied by using ion-beam epitaxial crystallization (IBIEC) of Fe-implanted Si(001) samples. By employing Rutherford backscattering/channeling spectrometry and transmission electron microscopy it was possible to determine that the IBIEC process produces a γ-, α-, and β-FeSi2 phase sequence, with increasing Fe concentration along the implantation profile. The critical concentrations for γ→α and α→β phase transitions are 11 and 21 at. %, respectively. A study of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…2d), and plate-like nanoparticles rotated with respect to the Si matrix (Fig. 2e), as previously reported (Lin et al, 1994;Behar et al, 1996). The sphere-like nanoparticles form coherent interfaces with the Si matrix, while the platelike ones are elongated along the Sih112i directions when projected along Sih110i.…”
Section: Research Paperssupporting
confidence: 61%
“…2d), and plate-like nanoparticles rotated with respect to the Si matrix (Fig. 2e), as previously reported (Lin et al, 1994;Behar et al, 1996). The sphere-like nanoparticles form coherent interfaces with the Si matrix, while the platelike ones are elongated along the Sih112i directions when projected along Sih110i.…”
Section: Research Paperssupporting
confidence: 61%
“…It is in close agreement with 5.95 deg of the (101) peak of the powdered a-Fe 2 Si 5 in Figure 8(d), although the diffraction angle is slightly decreased due to the lattice expansion at the elevated temperature. Since the diffraction in Figure 8(b) is far from that of 4.53 deg for (111) or 7.40 deg for (220) in the fluorite structure of the metastable cubic c-FeSi 2 , [12] no clear evidence of c-FeSi 2 was found. At the limited time and spatial resolutions, the initial phase that formed at the early stage of the recalescence was the tetragonal a-Fe 2 Si 5 .…”
Section: Experimental Methodsmentioning
confidence: 82%
“…In this alloy system, it was reported that c-FeSi 2 with a cubic structure can be formed in the heteroepitaxial thin layer on the Si substrate. [12] Hence, in the present experiment, the in-situ X-ray diffraction analysis was conducted to identify the phase that can be formed at an early stage of recalescence. Figure 8 shows the result of the in-situ X-ray diffraction taken at BL-11XU in Spring-8, where Figure 8 Figure 8(b).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[11 2] (straight lines) and [100] (dotted line) net patterns (Behar et al, 1996;Vouroutzis et al, 2008). As the SAED measurements have identified two crystalline phases, the near-surface precipitated layer should contain -FeSi 2 nanoparticles.…”
Section: Wwwintechopencommentioning
confidence: 99%